The family Sematophyllaceae (Bryopsida) in Australia. Part 1: Introduction, family data, key to genera and the genera Wijkia, Acanthorrynchium, Trismegistia and Sematophyllum - Ramsay, H.P. (2014)
Journal of the Hattori Botanical Laboratory